(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
Hebridean sites of the coastal sand cliffs and associated machair, or sandy plain have been known for many years. Artefacts and ecofacts of various types have long been collected from archaeological sites in the eroding sand-cliffs of the machairs of the Outer Hebrides. Early in 1983, personnel of the then Central Excavation Unit of Historic Scotland’s predecessor revisited very nearly all of the coastal archaeological sites then known in the Long Isle, with the specific task of identifying those at immediate threat from coastal erosion and of assessing the feasibility of their excavation or preservation. Some 32 sites were seen to be undergoing active erosion; at nine of them preservation was not being pursued and excavation was feasible. These sites were of two morphotypes: sites exposed in roughly vertical sand-cliffs and sites exposed over relatively large horzontal areas of sand deflation. It was decided to examine one sand-cliff site along its exposed face. The site selected was Balelone in North Uist, its excavation designed to explore both the problems associated with the excavation of deep midden sites with complex stratigraphy and the not-inconsiderable problems of excavation in sand. In the light of the Balelone trial excavation, a new approach was called for. A structured approach aimed firstly at establishing the three-dimensional extent of the sites to be examined. Four sites were then sampled in locations at Baleshare (NGR: NF 776 615), Hornish Point (NGR: NF 758 472), South Glendale (NGR: NF 798 143) and Newtonferry (NGR: NF 89511 78288) within a rigorously-defined research framework.